2005
DOI: 10.1111/j.1751-0813.2005.tb13306.x
|View full text |Cite
|
Sign up to set email alerts
|

Infectious bovine keratoconjunctivitis vaccine development

Abstract: Infectious bovine keratoconjunctivitis is a common and highly contagious ocular disease affecting cattle worldwide. The tremendous economic losses attributable to this disease warrant continued investigation into methods of prevention. Multiple virulence factors have been linked to the primary aetiologic agent, Moraxella bovis. Efforts to develop an efficacious vaccine have primarily focused upon the use of surface pili or cytolysin to stimulate host immunity; however, M. bovis possesses other virulence determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
0
9
0
2
Order By: Relevance
“…The response to the vaccine therefore may not have been protective. There is no consensus about the immunoglobins and antigens needed to induce a protective immune response . The results of the meta‐analysis suggest that, despite good evidence that M. bovis is a cause of IBK, M. bovis autogenous vaccines consistently fail to offer protection.…”
Section: Discussionmentioning
confidence: 99%
“…The response to the vaccine therefore may not have been protective. There is no consensus about the immunoglobins and antigens needed to induce a protective immune response . The results of the meta‐analysis suggest that, despite good evidence that M. bovis is a cause of IBK, M. bovis autogenous vaccines consistently fail to offer protection.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, because of the pilin variability between groups, the vaccine will not protect against infection with all strains in Australia, but there are no more efficacious vaccines currently commercially available. Data has been published on cytolysin based vaccines, and while these vaccines are likely to be cross protective against all serogroups of Moraxella bovis , the protection afforded is also incomplete 32 . The impact of vaccination on the national incidence of disease is unknown, but this will be influenced by the proportion of producers who elect to use the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous work we demonstrated that this could be due to the piliation loss that occurs as a consequence of the shear forces generated in cell environments when they are grown in mechanically stirred bioreactors [15]. Therefore, in M. bovis vaccine production, it is crucial to monitor cell-bound pili levels during bacterial growth to verify whether the bacterial cells produced maintain their immunogenic properties [11,15,17]. Consequently, we tested if piliation levels of samples withdrawn from stirred bioreactors could be estimated by the FT-IR ANN-based system developed.…”
Section: Quantification Of Piliation Level By An Ann Modelmentioning
confidence: 99%
“…After several vaccines trials it was demonstrated that prophylaxis relies so far largely on vaccines formulated with whole highly piliated M. bovis cells [11,12]. Rapid and reliable detection and quantification of the piliated phenotype in M. bovis is crucial to guarantee the efficacy of vaccine formulations and also important for any study of pathogenicity and epidemiology of IBK [11]. Current techniques for identifying piliated or nonpiliated cells include electron microscopy, slide agglutination (SA), tandem-crossed immunoelectrophoresis (TCIE) and immunological tests such as immunodiffusion and enzyme-linked immunosorbent assay (ELISA) [16][17][18].…”
mentioning
confidence: 99%
See 1 more Smart Citation